17-year trends in incidence and prognosis of cardiogenic shock in patients with acute myocardial infarction in western Sweden. (15th April 2015) - Redfors, B.; Angerås, O.; Råmunddal, T.; Dworeck, C.; Haraldsson, I.; Ioanes, D.; Petursson, P.; Libungan, B.; Odenstedt, J.; Stewart, J.; Lodin, E.; Wahlin, M.; et al.
Abstract: Background: Cardiogenic shock remains the leading cause of in hospital death in acute myocardial infarction (AMI) and is associated with a mortality rate of approximately 50%. Here we investigated the 17-year trends in incidence and prognosis of AMI-induced cardiogenic shock in Västra Götaland in western Sweden, an area with approximately 1.6 million inhabitants. The study period includes the transition from thrombolysis to primary percutaneous coronary intervention (PCI) as the region-wide therapy of choice for patients with ST-elevation myocardial infarction (STEMI). Methods: Data on patients hospitalized in cardiac care units in Västra Götaland, Sweden between 1995 and 2013 were obtained from the Swedish Websystem for Enhancement of Evidence-based Care in Heart Disease Evaluated According to Recommended Therapies (SWEDEHEART). We determined the incidence of cardiogenic shock among patients diagnosed with AMI and the risk of death associated with developing cardiogenic shock. We fitted logistic regression models to study which factors predicted post-AMI cardiogenic shock. Analyses were performed on complete case data as well as after multiple imputation of missing data. Results: Incidence of cardiogenic shock as a complication of AMI declined in western Sweden in the past decade, from 14% in 1995 to 4% in 2012. The risk of dying once cardiogenic shock had developed increased during the study period (p < 0.01). Patients presenting with STEMI were more likely to develop cardiogenic shock than patients presenting with non STEMI (p < 0.001). Conclusions: The incidence of cardiogenic shock has declined but cardiogenic shock carries a worse prognosis today than in 1995. Highlights: Sweden has a national system of medical and healthcare quality registries. These contain individualized data on risk factors, diagnoses, interventions and outcome. We present data on 44, 414 patients with acute myocardial infarction. 3, 654 patients developed cardiogenic shock. Incidence of cardiogenic shock decreased but prognosis worsened over the study period.